Needs for rural research in the Northern Finland context - Muilu, Toivo (Journal of Rural Studies, 2010)
The aim of this paper is to discuss the needs and demands which rural research faces at the interface between research and development. The case study area is northern Finland, which constitutes the most remote and sparsely populated areas of the European Union. This paper is based on the tradition of rural research since the 1980s in connection with the development of programme-based rural and regional policy. Rural researchers are desired actors in rural and regional development projects and programmes both at the national and regional level, but their challenge is to fulfil both academic standards of their background research organization and the often very practical needs of local and regional rural development actors. According to the opinions of rural actors in northern Finland, the definition of rural research is somewhat unclear and multidisciplinarity of rural research seems to give a free hand to carry out many kinds of research under the title. The needs and demand for rural research(ers) are quite practical and are mostly connected to the creation of new job opportunities outside primary production and development of villages via proposals given by researchers. The major result of this study is that rural research is highly appreciated both in programmes and among actors on the field , although the real role given to research remains unclear in most cases. v 2010 ok